Reconstruction of Arabic calligraphy by using Wang-Ball curves / Noorehan Awang ... [et al.] - Awang, Noorehan; Mohd Zauri, Aida Safiya; Jamil, Nur Fardila; Ghazalir, Fatin Najihah (UiTM Cawangan Negeri Sembilan, 2021)
The Wang-Ball curve conveniently can be used in applications in Computer-aided design (CAD) domain such as image extraction, protile approximation, fairing, smoothing and modelization. Rational Wang-ball which is derived from non-rational Wang-ball curves, where it has been proven that a rational Wang-ball curve is a rational Bezier curve of the same degree and vice versa. A recursive algorithm for plotting rational Bezier and Wang-ball is obtained by the de Casteljau and Wang algorithm using homogeneous coordinates and an efficient algorithm for evaluating a rational Wang-ball curve is attained and has a linear time complexity (Dejdumrong et al., 2001). Arabic calligraphy was initially an instrument for correspondence, yet with time, it started to be utilized in engineering, adomment and other structure. It is one of the art phenomena in the history of the revitalization of traditional art in the contemporary world. The outline of the calligraphy, mostly Arabic outline, was usually in quadratic and cubic degree. Therefore, the reconstruction of arabic font for degrees more than third degree for Wang-Ball curve was taken into consideration.